Analisis Kesiapsiagaan, Kerentanan dan Ketahanan Masyarakat dalam Menghadapi Bencana Alam: (Studi Kasus di Desa Tegaltirto) - Rita Mulyandari (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the community's preparedness in facing natural disasters in Tegaltirto Village through indicators that include preparedness, vulnerability, and social resilience. Based on data collected through surveys and field observations in several hamlets, the analysis is conducted using data on preparedness values, vulnerability, and social resilience to provide an overview of how ready the community is to face natural disasters. The results of this study are expected to provide recommendations for improving community preparedness for natural disasters and contribute to disaster mitigation planning in the field of civil engineering.